FORMULASI ABON IKAN LELE DUMBO (Clarias gariepinus) DAN RUMPUT LAUT (Eucheuma cottoni) RENDAH KALORI - Rania Nisrina Hanifah, - (2022)
African catfish (Clarias gariepinus) and seaweed (Eucheuma cottoni) have a low calorie content, this is suitable for processed floss which is low in calories and can be used as a supporting food for people who are running a weight loss program. The aims of this study were to determine the formulation of low-calorie catfish shredded and could be used as a food to support weight loss programs, and to determine the level of preference between commercial shredded fish and low-calorie shredded fish. This study used an experimental method with 3 treatments, namely, F1 with a formulation of 100% African catfish and 0% seaweed (Eucheuma cottoni), F2 with a formulation of 75% African catfish and 25% seaweed (Eucheuma cottoni), and F3 with formulation of 50% African catfish and 50% seaweed. The variables observed in this study included water content, fiber content, protein content, fat content, carbohydrate content, ash content, calories, and organoleptic tests. Techniques of data analysis using analysis of variance. The results of the prosimate test of shredded African catfish were, the water content of F1 was 18.05%, F2 was 13.48%, and F3 was 10.61%. The protein content of F1 was 58.84%, F2 was 53.56%, and F3 was 39.41%. Carbohydrate content F1 3.61%, F2 12.39%, and F3 20.38%. Fat content of F1 is 14.24%, F2 is 10.38%, and F3 is 8.67%. Ash content of F1 2.99%, F2 4.89%, and F3 9.23%. The fiber content of F1 is 1.28%, F2 is 5.30%, and F3 is 11.70%. The results of this study showed a small calorie shredded treatment at 100 grams and the calorific value of F1 treatment was 375 kl, F2 was 352 kl, and F3 was 362 kl. The results of the organoleptic test showed significant differences in the indicators of taste, color, and texture. There was no significant difference in the aroma indicator for each treatment. Abon African catfish with the addition of seaweed can be used as a low-calorie shredded formulation for weight loss programs.